Oral Language Skills of Elementary School Students to Support Multiliteracy Learning in the Digital Era - Lestari, Dewi Tri; Kusumaningrum, Shirly Rizki; Anggraini, Ade Eka; Dewi, Radeni Sukma Indra (Indonesian Values and Character Education Journal, 2024)
Students' oral language skills are very important in the digital era, and technology and communication have developed rapidly by presenting spoken language content that is popular with students. Multiliteracy learning refers to the multicontext aspect, which means learning uses various contexts or broad topics. In the multimedia aspect, multiliteracy learning uses various media. This research uses a case study design with the aim of exploring the oral language skills of elementary school students in the digital era to support multiliteracy learning. The data in the research was collected through several collection techniques in the form of questionnaires, observations and interviews. The data of this study were analysed using a qualitative approach with thematic analysis techniques. The research results show that students' oral language skills in this digital era are still limited to non-formal speaking skills. Talking content comes from shows that are watched, namely short dramas, advice, food review videos, other entertainment content. The type of text used in oral language learning is only printed text, which in their daily lives students often watch content on social media such as WhatsApp, Tiktok, snackvideo and YouTube. Students prefer short, interesting videos, with a few activities that involve thinking skills. Listening and speaking activities through these sources can be included in learning according to a multiliteracy context so that it is more meaningful for students.